2013
DOI: 10.3109/15368378.2013.773909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extremely low frequency electromagnetic field on the health of workers in automotive industry

Abstract: Survey and check-up data suggest that exposure to ELF-EMFs might have effects on the nervous, cardiovascular, liver, and hematology system of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…These changes may indicate the high vulnerability of brain (Cao et al, 2004;Martinez-Samano et al, 2012 andGhanbari et al, 2016) and liver (Liu et al, 2013 andKivrak et al, 2017) and their susceptibility to oxidative stress (Ragy, 2015). The results corroborate the findings of Samta et al (2017) that the exposure of rats to 900MHz EMR for 2hr daily for 3 months causes a considerable damage in the liver, and brain.…”
Section: Discussionsupporting
confidence: 78%
“…These changes may indicate the high vulnerability of brain (Cao et al, 2004;Martinez-Samano et al, 2012 andGhanbari et al, 2016) and liver (Liu et al, 2013 andKivrak et al, 2017) and their susceptibility to oxidative stress (Ragy, 2015). The results corroborate the findings of Samta et al (2017) that the exposure of rats to 900MHz EMR for 2hr daily for 3 months causes a considerable damage in the liver, and brain.…”
Section: Discussionsupporting
confidence: 78%
“…The hematological effects of chronic exposure to ELF-EMFs in animals and humans have been studied (Cakir et al, 2009; Nadimi et al, 2017). Liu et al (2013) reported that the exposure of employees to ELF-EMFs increases the number of white blood cells (WBCs) and lymphocytes but decreases the mean platelet volume and hematocrit.…”
Section: Introductionmentioning
confidence: 99%
“…Recently; several studies have been performed to verify direct effects exerted by ELF-EMFs on living cells functions. Although the results have been somewhat controversial, a variety of cell responses have been observed involving proliferation and differentiation [1][2][3], gene expression [4][5][6], modulation of the membrane receptors functionality [7,8] and free radicals' generation [9][10][11]. In 2002, the IARC classified ELF-EMFs as a "possible human carcinogen" and the decision IARC was supported by the WHO in 2007 [12].…”
Section: Introductionmentioning
confidence: 99%